PENGARUH PERTUMBUHAN EKONOMI, INFLASI, JUMLAH UANG BEREDAR (M2) DAN BI RATE TERHADAP TABUNGAN MUDHARABAH PADA PERBANKAN SYARIAH DI INDONESIA PERIODE 2005 - 2014 - PANORAMA, MAYA MAYA (Islamic Economics Program, Faculty of Islamic Economics and Business, 2016)
This research show that independent variable (PE, Inflation, JUB, and BI Rate ) simultaneously has significantly effect to dependent variable (Tabungan Mudharabah. This can be proved by significant value 0.000. Based on the test partially economic growth variable has a negative effect and not significant to Tabungan Mudharabah that showed by T test is 11.262. Inflation variable partially showed that has a negative effect and not significant to Tabungan Mudharabah that showed by T testing is -.391. Jumlah Uang Beredar (JUB) variable partially has positive effect and significant to Tabungan Mudharabah that showed by T test is 81.202. BI rate variable partially has positive effect and not significant to Tabungan Mudharabah that proved by T test is 1.306.Key word: economic growth, JUB , BI rate, Tabungan Mudharabah